The process of implementing the role of social workers in the rehabilitation of children in conflict with the law due to deviant behavior in gang fights - Zalfa Fakhirah; Sari Viciawati Machdum (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Juveniles in conflict with the law (ABH) involved in gang fights represent a distinct challenge for social workers, as these cases are characterized by collective violence rooted in peer pressure, solidarity, and revenge. Unlike other cases of deviant behavior, such as theft or drug abuse, gang fights are often repetitive, organized, and tied to self-affirmation. Social workers play multidimensional roles, ranging from protection and service provision to counseling, advocacy, mediation, and reintegration efforts, requiring a comprehensive and adaptive intervention approach. Methods: This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, field observations, and document reviews with six senior and junior social workers who directly handled ABH cases involving gang fights. Findings: The research findings reveal that interventions by social workers involve several stages, including relationship building, biopsychosocial assessment, individualized service planning, psychosocial interventions, legal process accompaniment, and reintegration efforts. Social workers use empathetic and family-oriented approaches to foster trust while providing services such as counseling, therapy, values education, and vocational training. Rehabilitation strategies emphasize strengthening self-control, emotional management, and resilience against peer influence. Obstacles identified include heavy workloads due to ATENSI service responsibilities and limited time for intensive interaction with ABH. Conclusion: Social workers serve as key agents of change in rehabilitating juveniles involved in gang fights. Their roles extend beyond rehabilitation within institutions to include reintegration into families and communities, aiming to build social support systems that prevent recidivism. Effective interventions require not only technical expertise but also adaptive, reflective, and participatory approaches aligned with the children’s complex social dynamics. Novelty/Originality of this article: This study provides unique insights into the role of social workers in handling ABH engaged in gang fights, a relatively underexplored area compared to other forms of juvenile delinquency. It highlights the complexity of interventions required, showing how social workers integrate legal accompaniment, psychosocial services, and community reintegration strategies to address the multifaceted challenges of collective juvenile violence.